An integrated approach to identification and conservation of medicinal plants in the tropical forest - A Brazilian experience - Di Stasi, Luiz Claudio [UNESP] (Cambridge University Press (CUP), 2005)
An integrated and interdisciplinary research programme with native medicinal plants from tropical forests has been performed in order to obtain new forest products for sustainable use in regional markets vis-à-vis ecosystem conservation. For the success of this programme ethnopharmacological studies are very important with respect to (i) identification of useful plants including medicinal and aromatic species; (ii) recuperation and preservation of traditional knowledge about native plants; and (iii) identification of potential plants with economic value. The plants are selected with a view to evaluate efficacy and safety (pharmacological and toxicological studies), and phytochemical profile and quality control (phytochemical and chromatographic characterization). These studies are very important to add value to plant products and also to mitigate unscrupulous exploitation of medicinal plants by local communities, since multiple use of plants represents an excellent strategy for sustaining the tropical ecosystem through ex situ and in situ conservation. Thus, conservation of tropical resources is possible in conjunction with improvements in the quality of life of the traditional communities and production of new products with therapeutic, cosmetic and 'cosmeceutic' value. © NIAB 2005.
Keywords: Ethnopharmacology; Ex situ conservation; In situ conservation; Medicinal plants; Sustainable management; Tropical forest